Challenges of university regionalization in Costa Rica - Chacón, Fernando Villalobos (2019)
One of the most relevant contemporary challenges for Governments is to achieve a successful regionalization ofpublic politics. Two of the guiding principles of universities should be the search for equity and social inclusion.To be able to fulfill this, universities should eagerly foster the transfer of programs and legal authority to the regions,instead of favoring centralism to the so called “university metropolis”, such has been the tendency in Latin Americaand Costa Rica. The search for an integral regional development must be strengthened by means of a social agreementamong different social figures. In Costa Rica in the last decades, public universities have been able to increasethe educational coverage, the quota, and the allocated budget to the regional headquarters. In spite of these efforts,the investment in the university regional headquarters continues being insufficient and contrasting against the oneallocated to the central headquarters.